The Effect of Work Environment, Compensation and Work Stress on Turnover Intention at PT. Bank Modern Express Ambon Branch - Souhoka, Semuel (Eastasouth Institute, 2025)
This study aims to analyze the influence of work environment, compensation, and work stress on employee turnover intention at PT. Modern Express Bank, Ambon Branch. High turnover intention can be detrimental to the company, especially in terms of human resource stability and recruitment costs. The method used in this study is a quantitative approach with a survey design. The research sample consisted of 40 employees selected using a saturated sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression to determine the effect of each independent variable on turnover intention. The results of the study indicate that work environment, compensation, and work stress simultaneously have a positive and significant effect on turnover intention. Partially, work environment variables have the most dominant influence on turnover intention, followed by work stress and compensation. The results of this study provide important insights for the management of PT. Bank Modern Express, Ambon Branch to improve work environment conditions, provide better compensation, and manage work stress to reduce employee turnover intention. Therefore, companies need to design policies that can improve the quality of the work environment, adjust compensation to employee expectations, and implement programs to reduce work stress in order to retain quality employees.